Ask the Experts: Hoarding disorder. (February 2014) - Nordsletten, Ashley E; Mataix-Cols, David
Ashley Nordsletten is a post-doctoral researcher at the Karolinska Institutet (Stockholm, Sweden). She obtained her doctorate in psychology from the Institute of Psychiatry, King's College London (London, UK) where her studies focused on the nosology, epidemiology and assessment of hoarding disorder. David Mataix-Cols is professor of child and adolescent psychiatric research at the Karolinska Institutet (Stockholm, Sweden). He runs a program of research aimed at understanding the causes of anxiety, obsessive–compulsive and related disorders across the lifespan and the development of better and more cost-effective treatments for these problems. He is an author of over 150 peer-reviewed publications and a recipient of multiple grants and awards from the UK, USA, EU, Sweden and Spain. As advisor to the DSM-5 Obsessive–Compulsive Spectrum Sub-Work Group he was instrumental to the inclusion of hoarding disorder as a separate mental disorder in the nomenclature.